THE WILLIAM'S EXERCISES ADDITION ON MICRO WAVE DIATHERMY, TRANSCUTANEUS ELECTRICAL NERVE STIMULATION AND ABDOMINAL EXERCISES INTERVENTION REDUCE OF LOWER BACK PAIN AMONG PATIENT WITH LUMBAR SPONDYLOSIS - SUBADI, I MADE (Majalah Ilmiah Fisioterapi Indonesia; Vol 1 No 1 (2013): Majalah Ilmiah Fisioterapi IndonesiaDO - 10.24843/MIFI.2013.v01.i01.p06)
Low back pain in Spondylosis Lumbaliscondition caused by a decrease in disc space and thenarrowing of the intervertebral foramen. And a decrease in disc space narrowing of theintervertebra lforamen can produce irritation of the nerve roots causing low back pain isspreading until to the leg and foot. The purpose of this study was to determine how much toincrease the effectiveness of pain reduction on added William’s Exercises on interventionMWD, TENS,and Abdominal Exercises.Experimental studies have been done with thedesign of randomized pre test and post test group design. Sample size of 26 is divided intotwo groups of 13 persons each. Group I with intervention of MWD, TENS, AbdominalExercises,whereas group II with intervention of MWD, TENS, Abdominal Exercises andWilliam’s Exercises. The data was collected by measuring the intensity of pain using theVAS, at the time before and after intervention, then performed with different test t-test(Paired t-test and Independent t-test). The results showed significant effect of each groupafter intervention to decrease pain intensity p=0.000 (p <0.05). But the average level of pain after intervention on group II seems more effective to reduce pain. Added William’sExercises in patients with Spondylosis Lumbalis in function stretching erector spine muscleand reduce lock facet joint, so will be decrease the pain.So it is advisable to add William’sExercises a combination of giving MWD, TENS and Abdominal Exercises reduce low backpain in patients with Spondylosis Lumbalis.
Keywords: MWD, TENS, Abdominal and William’s Exercises, Pain,Spondylosis Lumbalis